2012
DOI: 10.4490/algae.2012.27.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics of the seagrass, Zostera marina in Jindong Bay on the southern coast of Korea

Abstract: Growth dynamics of the seagrass, Zostera marina were examined at the two stations (Myungju and Dagu) in Jindong Bay on the southern coast of Korea. Eelgrass leaf productivities, underwater irradiance, water temperature, dissolved inorganic nitrogen (DIN) in water column and sediments, and tissue carbon (C) and nitrogen (N) content were monitored monthly from March 2002 to January 2004. Underwater irradiance fluctuated highly without a clear seasonal trend, whereas water temperature showed a distinct seasonal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In this study, the productivities of Z. marina at both study sites exhibited significant seasonality (p b 0.001), increasing during the spring and summer and decreasing during the fall and winter. Similar trends in the biomass and productivity of Z. marina have been reported by several studies (Kim et al, 2012, Lee et al, 2004, Lee et al, 2005. The irradiance at the Dongdae Bay and Ojiri seagrass beds did not change significantly between March and June (Fig.…”
Section: Environmental Factors Influencing the Productivity Of Z Msupporting
confidence: 85%
“…In this study, the productivities of Z. marina at both study sites exhibited significant seasonality (p b 0.001), increasing during the spring and summer and decreasing during the fall and winter. Similar trends in the biomass and productivity of Z. marina have been reported by several studies (Kim et al, 2012, Lee et al, 2004, Lee et al, 2005. The irradiance at the Dongdae Bay and Ojiri seagrass beds did not change significantly between March and June (Fig.…”
Section: Environmental Factors Influencing the Productivity Of Z Msupporting
confidence: 85%
“…In all treatments, NCP increases during the morning were more pronounced than during the afternoon, just after the photoinhibition process, as shown by the differences in the slopes of NCP versus irradiance obtained from the morning and the afternoon incubations. It is important to note that NCP values may vary seasonally, since the length of the day, irradiance, and temperature, which are factors known to affect metabolic rates (MacLeod and Barton, 1988;Lee et al, 2007;Kim et al, 2012), will all vary as there is variation in hours of light, light intensity, and temperature. Therefore, future studies assessing the net community production and community metabolism of seagrass meadows should include the seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…N levels in Z. marina belowground compartments from Belyounech bay meadow (0.74 %DW, average of root and rhizome values) are low when compared to other places (Supplementary material Table S5). Kim et al (2012) reported a seasonal variation of N levels in Z. marina belowground compartment, with levels ranging from 5.50 %DW in winter to 0.50 %DW in summer and spring. However, the primary production of seagrass compartments can be high despite low N concentration in the plant (Pedersen and Borum, 1992;Gobert et al, 2002;Cabaço et al, 2013).…”
Section: Discussionmentioning
confidence: 97%